ANALISIS KANDUNGAN DIOSMIN TANAMAN SELEDRI PADA BERBAGAI MEDIA TUMBUH - Mohamad Ana Syabana; Edi Jauhari PK; Elly Surahadikusuma (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACTThe celery plant well known as herbs especially because of celery’s odor and it also have a lot of positive impact to health, for example antidiuretic, antiplasmodic and antiinflammatory. This impact because of celery secondary metabolite one of them is diosmin. The non-optimum plant growthenvironment will induce secondary metabolite production. This research aim is to find the plant medium that will produce most diosmin content. Celery was planted on six kind of plant medium that was dolomite lime andosol, compost andosol, sand andosol, dolomite lime podsolic, compost podsolic and sand podsolic media. Six weeks after growing in a green house wich temperature 27,3 0C. Selery was harvested and dried on the oven. Futhermore the diosmin content was measured qualitative by TLC and Quantitative by HPLC. The highest diosmin content is 1754,90 ppm showed on dried celery from dolomite lime andosol media, from dolomite lime podsolic media is 1424,57 ppm, from compost andosol media is 1134,2 ppm and the lowest from sand andosol.Key words: celery, diosmin, plant media, HPLC